First Records of Possibly Human Pathogenic Rickettsia Species in Bat Ticks, Carios vespertilionis, in Sweden - Eszter Tompa; Thomas G. T. Jaenson; Peter Wilhelmsson (Microorganisms, 2023)
The Soprano pipistrelle bat, Pipistrellus pygmaeus, is a common species in large parts of Sweden. Many of its natural habitats are near human habitations. This creates opportunities for ticks infesting these bats to encounter humans and possibly transmit zoonotic pathogens by tick bites. The bats are often infested with Carios vespertilionis, a tick species that, in addition to bats, has been recorded to bite humans on occasion. This study aimed to investigate if C. vespertilionis acts as a reservoir for Anaplasma phagocytophilum, Neoehrlichia mikurensis, Tick-borne encephalitis virus, and species of Babesia and Rickettsia and to improve currently used conventional PCR protocols for molecular species determination of Rickettsia spp. Ninety-two C. vespertilionis ticks were collected from underneath a bat-box harbouring P. pygmaeus. Pathogen-specific PCR assays showed that 58.4% were positive for Rickettsia spp. and negative for the other pathogens analysed. Phylogenetic analyses indicate that the species belong to R. parkeri, R. conorii, R. slovaca, R. sibirica subsp. mongolotimonae, R. rickettsii, and a hitherto uncultured Rickettsia sp. Several of these species are considered pathogenic to humans. Given the ecology and behaviour of C. vespertilionis, it may be a vector of these rickettsiae among bats and occasionally humans. To determine the Rickettsia species with certainty, and to determine if C. vespertilionis may be a reservoir and vector of the Rickettsia spp., further studies are needed.